Nettverkserfaringer hos personer med behov for arbeidsrettet rehabilitering - Evensen, Aud; Brataas, Hildfrid V. (Nordisk Tidsskrift for Helseforskning, 2015)
This article analyzes network experiences of persons who have participated in a program for rehabilitation back to work. The study was qualitative, with a descriptive and interpretive research design, using qualitative in-depth interviews. Results show how the informants related to their network before rehabilitation and how they during the rehabilitation opened up to learn about their own network understanding. There were noticeable changes in their way of how to deal with their networks. There is a need of more knowledge about how persons in need of rehabilitation back to work experience and relate to different networks.